Dynamics of strategic information transmission in social networks - Manuel Förster (Theoretical Economics, 2019)
We develop a dynamic framework of strategic information transmission through cheap talk in a social network. Privately informed agents have different preferences about the action to be implemented by each agent and repeatedly communicate with their neighbors in the network. We first characterize myopic (best response) equilibria as well as fully informative myopic equilibria. Second, we provide a sufficient condition for the existence of a fully informative farsighted (perfect Bayesian) equilibrium. Fully informative myopic and farsighted equilibria essentially take a particular simple form: all communication is truthful along a subnetwork that is a tree. We also consider societies in which both myopic and farsighted agents are present and analyze equilibrium welfare. Furthermore, we extend our model to public communication and investigate the implications of our results for the design of institutions. Finally, our analysis reveals that myopic equilibria tend to Pareto dominate farsighted equilibria, in particular if a social planner has designed the network optimally.
Keywords: C72; D82; D83; D85; 330; Cheap talk; information aggregation; learning; social networks; strategic communication